Metabolomics reveals that aldose reductase activity due to AKR1B10 is upregulated in hepatitis C virus infection. Issue 7 (9th December 2014) - Semmo, N.; Weber, T.; Idle, J. R.; Beyoğlu, D.
Summary To understand the changes in the metabolome of hepatitis C virus (HCV)‐infected persons, we conducted a metabolomic investigation in both plasma and urine of 30 HCV‐positive individuals using plasmas from 30 HCV‐negative blood donors and urines from 30 healthy volunteers. Samples were analysed by gas chromatography–mass spectrometry and data subjected to multivariate analysis. The plasma metabolomic phenotype of HCV‐positive persons was found to have elevated glucose, mannose and oleamide, together with depressed plasma lactate. The urinary metabolomic phenotype of HCV‐positive persons comprised reduced excretion of fructose and galactose combined with elevated urinary excretion of 6‐deoxygalactose (fucose) and the polyols sorbitol, galactitol and xylitol. HCV‐infected persons had elevated galactitol/galactose and sorbitol/glucose urinary ratios, which were highly correlated. These observations pointed to enhanced aldose reductase activity, and this was confirmed by real‐time quantitative polymerase chain reaction with AKR1B10 gene expression elevated sixfold in the liver. In contrast, AKR1B1 gene expression was reduced 40% in HCV‐positive livers. Interestingly, persons who were formerly HCV infected retained the metabolomic phenotype of HCV infection without reverting to the HCV‐negative metabolomic phenotype. This suggests that the effects of HCV on hepatic metabolism may be long lived. Hepatic AKR1B10 has been reported to be elevated in hepatocellular carcinoma and in several premalignant liver diseases. It would appear that HCV infection alone increases AKR1B10 expression, which manifests itself as enhanced urinary excretion of polyols with reduced urinary excretion of their corresponding hexoses. What role the polyols play in hepatic pathophysiology of HCV infection and its sequelae is currently unknown.